Experimental and numerical study of the flammability limits in a CH4/O2 torch ignition system - Shynkarenko, Olexiy (2022)
The current work is devoted to studying combustion initiation inside the methane-oxygen torch igniter for a hybrid rocket motor. The ignition system can generate a wide range of power and oxidizer-to-fuel ratios. It has a self-cooled vortex combustion chamber with one fuel jet injector and one circumferential vortex oxidizer injector. The system adjusts the mass flow rates of the propellants through the control valves and organizes cooling of the wall and flame stabilization. Experimental analysis of the ignition limits was investigated on the laboratory test bench. The propellants’ pressure and mass-flow rates, combustion temperature, ignition delay, and spark frequency were controlled during the tests. The authors executed a series of tests with different propellants’ mass flow rates. As a result, the region of stable ignition was found as well as the regions of ignition failure or unreliable ignition. A previously validated numerical model was used to analyze the flow in the reliable ignition region and the ignition failures region. Several numerical simulations of the transient three-dimensional chemically reacting flow were implemented. Consequently, the ignition delay and the thermal impact on the combustion chamber wall were determined numerically. Results of the simulations were compared with theoretical and experimental data showing good correspondence.